Internalisasi Nilai-Nilai Keislaman Berbasis Pesantren Perspektif Sosial Kemasyarakatan - Slamet Arofik (rogram Studi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2020)
Islamic boarding schools are not only as religious-oriented educational institutions (tafaqquh fi al-din), but more than that, they teach the values ​​of life both religiously and socially oriented so that they have multi-complex duties and roles compared to other educational institutions. Islamic boarding schools do not only teach knowledge / knowledge in a cognitive manner, but go beyond that in an affective manner. praxis and actualizing it directly in real life so as to form a strong character that is able to bring students to become individuals who are ready to face the challenges of the times. The values ​​taught in the Islamic boarding school if concluded will shape the santri into someone with strong character as follows: 1. Obedient and obedient to religious and state orders; 2. Able to bring himself to be a person who is responsible both to himself and to his community; 3. Being a successful person in terms of hablun min al-Allah (relationship with Allah) and hablun min al-nas (relations between human beings); 4. Personal sensitive to the surrounding environment; 5. Become a person who has a spirit of nationalism